2014
DOI: 10.1128/aem.01048-14
|View full text |Cite
|
Sign up to set email alerts
|

The Key to Acetate: Metabolic Fluxes of Acetic Acid Bacteria under Cocoa Pulp Fermentation-Simulating Conditions

Abstract: c Acetic acid bacteria (AAB) play an important role during cocoa fermentation, as their main product, acetate, is a major driver for the development of the desired cocoa flavors. Here, we investigated the specialized metabolism of these bacteria under cocoa pulp fermentation-simulating conditions. A carefully designed combination of parallel 13 C isotope labeling experiments allowed the elucidation of intracellular fluxes in the complex environment of cocoa pulp, when lactate and ethanol were included as prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
94
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 71 publications
13
94
0
1
Order By: Relevance
“…Furthermore the AA labelling in the 24h and 48h samples showed very similar patterns as the one detected in Ap and Lp co-cultures using labelled glucose. Our results show that Ap synthesizes multiple AAs from lactate and are in agreement with earlier reports that lactate can serve as an important precursor for AA synthesis in other Acetobacteraceae (Adler et al, 2014). Interestingly, the average amount of 13 C-Ile synthesized from 13 C 3 -lactate was similar to that measured in the co-cultures of Ap and Lp synthesized from 13 C-glucose ( Figure 3 and 5 and Figure S5, S7 and S8), enforcing the similarity between the co-culture condition and the lactate Ap condition.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore the AA labelling in the 24h and 48h samples showed very similar patterns as the one detected in Ap and Lp co-cultures using labelled glucose. Our results show that Ap synthesizes multiple AAs from lactate and are in agreement with earlier reports that lactate can serve as an important precursor for AA synthesis in other Acetobacteraceae (Adler et al, 2014). Interestingly, the average amount of 13 C-Ile synthesized from 13 C 3 -lactate was similar to that measured in the co-cultures of Ap and Lp synthesized from 13 C-glucose ( Figure 3 and 5 and Figure S5, S7 and S8), enforcing the similarity between the co-culture condition and the lactate Ap condition.…”
Section: Resultssupporting
confidence: 93%
“…Concomitantly, this interaction also spurs the growth of Ap as this bacterium grows better in the fly in the presence of Lp. This positive effect of Lp on AA synthesis by Ap is best explained by the preferential use of lactate by Ap for the production of AAs (Adler et al, 2014) which coincidentally is one of the main metabolic byproducts produced and secreted by Lp. These metabolic interactions within the Ap/Lp community allow these two bacteria to create a "circular economy" in which they both optimally use the available nutritional resources provided by the host diet, allowing them both to overcome detrimental host diets and boosting their metabolic output.…”
Section: Discussionmentioning
confidence: 99%
“…The AAB metabolism irreversibly switches to overoxidation only when ethanol is depleted, as this metabolic pathway is repressed in the presence of ethanol . During cocoa bean fermentation, it has been shown that AAB can convert lactic acid into acetoin, which may be of benefit in lambic beer production too, as acetoin may contribute to the lambic beer aroma . The AAB also possess intracellular esterases, catalyzing the condensation of acetic acid and ethanol into ethyl acetate, a common ester of lambic beers …”
Section: Lambic Beersmentioning
confidence: 99%
“…105,106 During cocoa bean fermentation, it has been shown that AAB can convert lactic acid into acetoin, which may be of benefit in lambic beer production too, as acetoin may contribute to the lambic beer aroma. 69,107,108 The AAB also possess intracellular esterases, catalyzing the condensation of acetic acid and ethanol into ethyl acetate, a common ester of lambic beers. 109 Brettanomyces species Brettanomyces yeasts characterize the fourth phase of the lambic beer production process (after eight months of fermentation/maturation; Fig.…”
Section: Saccharomyces Speciesmentioning
confidence: 99%
“…For example, AAB can generate acetic acid through the direct metabolism of sugars (Swiegers and others ). According to Adler and others (), the formation of acetate is key in the development of desirable flavors in chocolate.…”
Section: Harvesting and Postharvest Processing Aspects That Affect Chmentioning
confidence: 99%